Proceedings of the 2008 ACM Conference on Computer Supported Cooperative Work 2008
DOI: 10.1145/1460563.1460675
|View full text |Cite
|
Sign up to set email alerts
|

Changes in use and perception of facebook

Abstract: As social computing systems persist over time, the user experiences and interactions they support may change. One type of social computing system, Social Network Sites (SNSs), are becoming more popular across broad segments of Internet users. Facebook, in particular, has very broad participation amongst college attendees, and has been growing in other populations as well. This paper looks at how use of Facebook has changed over time, as indicated by three consecutive years of survey data and interviews with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
186
2
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(217 citation statements)
references
References 22 publications
5
186
2
10
Order By: Relevance
“…Researchers have asked various questions to understand the uses of OSNs by adults, their specific behavior, and the psychology behind their behaviors. The findings of these studies support the notion that social behaviors online reflect offline behavior [41,42]. For instance, those who spent much time socializing offline are more likely to exhibit similar behavior on OSNs.…”
Section: Computer-mediated Social Lifesupporting
confidence: 74%
“…Researchers have asked various questions to understand the uses of OSNs by adults, their specific behavior, and the psychology behind their behaviors. The findings of these studies support the notion that social behaviors online reflect offline behavior [41,42]. For instance, those who spent much time socializing offline are more likely to exhibit similar behavior on OSNs.…”
Section: Computer-mediated Social Lifesupporting
confidence: 74%
“…6 Some early research on aggressive behavior online suggested that online personality could diverge from offline personality, 7 but others have argued that those studies were based on forms of media (e.g., flaming in chat rooms) in which users had no expectation for future interactions. 8 Supporting the idea that online social processes mirror those conducted offline, 9 recent research suggests that people largely use online tools to maintain their existing relationships, [10][11][12][13] people who are liked in offline context are also liked online, 14 and, mirroring offline findings, those who use OSNs more frequently also possess greater social capital. 15 Despite this research pointing to similar socialization processes in offline and online contexts, research focusing specifically on personality processes in online contexts is scarce.…”
Section: Introductionmentioning
confidence: 95%
“…Some research have also highlighted students' concern over academic use of these social media tools in terms of issues of privacy and identity management (Hoare, 2007;Hewitt & Forte, 2006;Szwelnik, 2008). Additionally, certain research findings seem to indicate that use of SNSs is mainly for social purposes (Boyd & Ellison, 2007;Lampe et al, 2008;Madge et al, 2009) with some students expressing their unease at the idea of their instructors having a presence in what these students view as their 'private personal space' (Szwelnik, 2008). Sandars and Schroter (2007) found that although students might be familiar with the new technologies for certain purposes, this does not mean that the use of these technologies would be translated into its use for teaching and learning.…”
Section: Literature Reviewmentioning
confidence: 99%